Islamic values on buying intention towards suspecting haram-content beverage productsin muslim majority countries: developing a conceptual framework - Haque, A. K. M. Ahasanul; Ahmed, Faruk; Kabir, SMH (World Academy of Islamic Management (WAIM), 2021)
In this study, a conceptual framework is developed to provide an insightful linkage between Islamic beliefs(personal, family, social,and institutional beliefs)and purchase intention towards haram-content suspected beverage products.Islam can aid in avoiding suspected haram-content beverage products for its power of haram-halal codes since alcoholism is prohibited in Quran. According to Usul-Al-Fiq, pork and other animal fat used in various food and beverage products are harams since eating pork is listed in haram codes in Quran.A comprehensive content analysis was accomplished to develop the hypotheses on the basis of reading materials and discussionswith several business professors and other academic sources.The study explored a significant role in the body of Islamic consumerism and in the realm of Islamic marketing practices.Muslim leaders could formulate and implement strategies to change the conventional organizationalimage into an Islamic organization image. This research is a prime effort to show how good Islamic values should be added to Muslim and non-Muslim organizations.